Synaptic connectivity of the cholinergic axons in the olfactory bulb of the cynomolgus monkey - Teresa eLiberia; José Miguel eBlasco Ibáñez; Juan eNácher; Emilio eVarea; Jose L Lanciego; Carlos eCrespo (Frontiers Media S.A., 2015)
The olfactory bulb of mammals receives cholinergic afferents from the horizontal limb of the diagonal band of Broca. At present, the synaptic connectivity of the cholinergic axons on the circuits of the olfactory bulb has only been investigated in the rat. In this report, we analyze the synaptic connectivity of the cholinergic axons in the olfactory bulb of the cynomolgus monkey (Macaca fascicularis). Our aim is to investigate whether the cholinergic innervation of the bulbar circuits is phylogenetically conserved between macrosmatic and microsmatic mammals. Our results demonstrate that the cholinergic axons form synaptic contacts on interneurons. In the glomerular layer, their main targets are the periglomerular cells, which receive axo-somatic and axo-dendritic synapses. In the inframitral region, their main targets are the granule cells, which receive synaptic contacts on their dendritic shafts and spines. Although the cholinergic boutons were frequently found in close vicinity of the dendrites of principal cells, we have not found synaptic contacts on them. From a comparative perspective, our data indicate that the synaptic connectivity of the cholinergic circuits is highly preserved in the olfactory bulb of macrosmatic and microsmatic mammals.